Maximizing precipitation hardening effect enables ultrahigh strength in a coarse-grained Mg-13Gd forging alloy - Dongdong Zhang; Hucheng Pan; Zhihao Zeng; Weineng Tang; Jingren Li; Hongbo Xie; Rongguang Li; Yuping Ren; Gaowu Qin (Journal of Magnesium and Alloys, 2024)
In this work, a new strategy for achieving ultrahigh strength in the coarse-grained Mg-Gd binary alloy via utilizing recrystallization texture hardening and maximizing precipitation strengthening has been reported. Forging at a much high temperature suppresses dynamic precipitation, enabling the super-saturation of Gd atoms in Mg matrix. This facilitates the formation of fully recrystallized grains with strong texture and induces an exceptionally high precipitation hardening in the following ageing. Therefore, the forged Mg-13Gd sample exhibited extraordinary tensile yield strength (TYS) of ∼430 MPa, in which ageing-induced TYS increment exceeds ∼210 MPa, as the highest record so far in precipitation-hardened Mg communities. These results provide important theoretical guidance for fabricating the large section and high-strength Mg components for industrial applications.